Health-promoting lifestyle and its relationship with health literacy of employees of zanjan University of medical sciences - Zahra Hajagharezaloo; Nasrin Jafari Varjoshani; Masoumeh Moqaddam; Ramezan Fallah (Zanjan University of Medical Sciences and Health Services, 2024)
Background: A health-promoting lifestyle and optimal health literacy are among the determining health promotion and maintenance sources. Objectives: The current study was conducted to determine the status of health-promoting lifestyle and its relationship with health literacy of employees of Zanjan University of Medical Sciences in 2020. Methods: This cross-sectional descriptive-correlational study was conducted on 308 administrative employees of faculties, hospitals, and health centers in Zanjan. The participants were included in the study using a stratified random sampling method. Three questionnaires, including the demographic information questionnaire, the standard Health-Promoting Lifestyle Profile II (HPLPII) questionnaire, and the Health Literacy for Iranian Adults (HELIA) questionnaire, were used to collect data. Data were analyzed using descriptive and inferential statistics (Pearson's correlation and stepwise regression) in SPSS 24. Results: The mean age of the employees was 36.51(7.29) years, and most of the participants were female (53.2%), married (80.8%), and had a bachelor's degree or higher (89.3%). The participants' health literacy score was at an adequate level 75.85 (12.23) and their lifestyle score was at a desirable level 137.22 (21.15). The relationship between health literacy dimensions and the lifestyle total score was positive and significant (p>0.05). Conclusion: According to the findings of the current study and the presence of a relationship between health literacy and lifestyle, particularly the predictive role of decision-making dimensions and accessibility of health literacy with the lifestyle of employees, it is suggested that programs be developed and implemented to empower the health literacy of employees.